Prevalence of Thyroid Disorder in Residents of Western Region of Nepal - Sharma, Preeti; Magar, Namarata Thapa; BK, Mahesh (International Journal of Applied Sciences and Biotechnology, 2021)
Thyroid disorder, such as goiter, hypothyroidism, and hyperthyroidism, are leading health problems in Nepal. Owing to geographical and environmental factors, iodine deficiency is prime cause of thyroid disorder. The objective of study to estimate the prevalence of thyroid disorder in residents of western region of Nepal (Pokhara valley). Materials & Methods: The study design was hospital based retrospective study. The data of T3, T4, TSH was collected from subject visiting Department of Biochemistry at Gandaki Medical College Teaching Hospital and Research Centre, Nepal. The samples was collected, serum was separated and thyroid hormones was assayed by Enzyme linked Immunosorbent assay kit from RFLC (India). Result: The total study population was 2248 cases of which 580 (male) and 1668 (female) were enrolled in the study. The prevalence of thyroid disorder was 22.42 % in western region. Subject with hypothyroidism was 12.41% (279) & subject with hyperthyroidism were 10.41% (234) respectively. Female subject of age (15-44) years had a hypothyroidism, i.e. 52.83% (112). About 73.15% (109 out of 149 subjects) were female cases suffered from subclinical hypothyroidism. The thyroid disorder found most prevalent in reproductive age group in female residents in our study. Conclusion: Hypothyroidism is prevalent in all age group of female residents of western region of Nepal.Our study conclude that hypothyroidism and subclinical hypothyroidism found more prevalent in reproductive age group in residents of western region of Nepal.Int. J. Appl. Sci. Biotechnol. Vol 9(3): 169-175